The characteristics and the energy behaviour of the residential building stock of Cyprus in view of Directive 2002/91/EC - Panayiotou, Gregoris; Kalogirou, Soteris A.; Florides, Georgios A.; Maxoulis, Christos N.; Papadopoulos, Agis M.; Neophytou, Marina K A; Fokaides, Paris A. A.; Georgiou, Gregoria; Symeou, A.; Georgakis, G. (My University, 2010)
The significance of the residential building sector in terms of energy consumption is well acknowledged. In this view the knowledge of the way the residential building stock of Cyprus behaves in terms of energy consumption is quite valuable since it will assist policy makers to formulate targeted measures aiming the improvement of energy efficiency and setting current legal standards and benchmarks in the energy performance certificate, a requirement of the 2002/91/EC Directive. Unfortunately, the existing knowledge on this subject is quite poor. As a remedy a research project supported by a national research grant is in operation since December 2008. This paper presents the outline, goals and methodology of this research project and the findings regarding the energy behaviour and other characteristics of the residential building stock of Cyprus. From the analysis of the results for 500 residential buildings, it seems that the energy demand and primary energy required is lower than that of other European countries. Moreover, it seems that the age of residential buildings has low correlation with the energy demand while in contrast with other Northern and Central European countries, it is clear that the contribution of cooling energy requirements to the overall energy demand is quite significant
Keywords: Energy performance, Directive 2002/91/EC, Cyprus; Operational rating; Residential building stock